DETERMINAN MINAT PEGAWAI PEMERINTAH DAERAH DALAM MELAKUKAN WHISTLEBLOWING - Toni Nurhadianto (TECHNOBIZ : International Journal of Business, 2022)
This study aims to examine the effect of job satisfaction, fair treatment, and cooperativeness on the intention to do whistleblowing. This study is primary data obtained through the distribution of questionnaires in 23 Regional Apparatus Organizations in Bandar Lampung City. The sample of this study was 90 respondents who were taken by purposive sampling technique. The method of analysis used multiple linear regression. The test results show that fair treatment and cooperativeness have a positive effect on the intention to do whistleblowing. Meanwhile, job satisfaction has no effect on the intention to do whistleblowing.